Pengaruh Material Plastik Terhadap Kekuatan Geser Pada Tanah Lempung - . Sazuatmo (Jurnal Teknik Sipil, 2011)
Clay is one of soil type, where the bearing capacity is low and water conten sensitivity highly. Where the water content is increased, their physical characteristic and mechanics ( chesion and internally priction ). Will decrease and on the dry condition will be in contrast. Manyefforts has been done to improve , especially clay. One of them is soil reinfort ced by plastics or plastic waste. In the research , a series of laboratory work has been done I.e atterberg limits test, grain size distribution , compaction and direct shear test. In the research it is made 18 vebriation of speci men i.e 3 size plastics ( 2 x 2 cm2, 2 x 1 cm2 dan 2 x 0.5 cm2 ) and the varying of plastics into clay ( 0%; 0,5%; 1,5%; 2% ; 2,5% ) the percentage of plastics is based on weight percentage to soris weight. The test result shows, waste plastics has enhanced shear strength of soil Â ( 84,538%), this increase to occur 2 X 2 Cm2 by 1 % plastic . and waste plastics in size 2 X 0,5 Cm2 has enhanced shear strength of soil ( 77,454 % ) by 1% plastic. For waste plastics in size 2 X 1 cm2 has enhanced shear strength of soil ( 54,894 % ) by 2,5 % plastics. The concolusion , plastics enhanced shear strength of soil.